The Impact of Corporate Governance Mechanisms on Environmental Disclosure Practices: Evidence from Manufacturing Industry in Bangladesh - Sumon Kumar Das; Diljahan Akter; Tanvir Hossain (Universitas Pasundan, 2021)
The current study identifies the impact of corporate governance mechanisms on environmental disclosure (ED) in Bangladesh. A total of 359 firm-year observations extracted from the annual reports of 86 listed manufacturing companies listed on the Dhaka Stock Exchange for the period from 2015 to 2019 were examined. Multiple linear regression analysis was performed to identify the driving forces of ED practices. This study found that foreign stockholdings, board size, and audit committee size significantly positively correlate with ED. However, surprisingly, more representation of independent directors in the boardroom and institutional ownership in share capital can actually reduce the extent of ED for our sample firms. These results provide a comprehensive understanding of the determinants of ED in an emerging country like Bangladesh and may prove useful for regulators, policymakers, and corporate managers. The data will assist other stakeholders in making relevant decisions. However, by providing the empirical facts of the underlying determinants of ED practices in developing countries’ manufacturing sector settings, the study provides a novel contribution to the current ED literature. To the best of the authors’ knowledge, this is the first study investigating the determinants of ED practices of the manufacturing industry based on the Global Reporting Initiative.